'I'm being pulled in too many different directions': academic identity tensions at regional public universities in challenging economic times. Issue 2 (1st February 2020) - Dugas, Daryl; Stich, Amy E.; Harris, Lindsay N.; Summers, Kelly H.
ABSTRACT: Faculty ( N = 205) at regional public universities (RPUs) in the United States were surveyed for self-reports of their primary academic identity (teacher, researcher) and qualitative descriptions of struggles related to their academic identity. Well-being and job satisfaction were examined as outcome measures of identity struggles. Participants were selected from RPUs in Illinois, a state with severe budget challenges, to assess the impact of financial pressures on academic identity at traditionally teaching-focused institutions. Responses were not uniform across faculty, with some reporting few identity struggles and others reporting difficulty managing, lack of institutional support, and feeling that something would need to 'give' eventually. Faculty who identified as researchers and who spent most of their time doing research reported the fewest struggles, while researchers who were not able to devote time to research most frequently reported distress. Implications and challenges to faculty work and strains on academic identity at RPUs are discussed.